Paths for retirement - Naqui, Maria; Selva, Clara; Méndez, Marta (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
The life of a person can be mainly divided in different stages. The stage of the labour life is the most important and significant, since it is the activity that occupies the most time of our lives and that generates more self-fulfilment. That is the reason why, when the stage of retirement arrives, many doubts and fears appear. The vision of this stage has been changing over the years (MonrealBosch, Perera, Martínez & Selva, 2017). In the past, the retirement was to rest, whereas nowadays retired people are looking for fun and entertainment with leisure activities (Escarbajal & Martínez, 2012). Authors as Bueno & Buz (2006) affirm that this moment can be faced with different attitudes: rejection, acceptance, opportunity or ambivalence. The adaptation to this new stage of the life cycle is influenced by various factors that can favour a better adjustment, as for example the social support (Sáez, Aleixandre & Meléndez, 1995). Those human or material resources that each person or family has to face a crisis situation will set their social support network (family, friends, co-workers, etc.). Regarding the diversity of situations related to retirement, organizations should start to care about the measures that they could implement to help their workers, since it is common to move towards retirement without knowing what options exist (Sahagún, Hermosillo & Selva, 2014). We face a situation of great complexity that concerns the entire society, because the number of retired people or next to retirement age increases day after day. In addition, this stage is often faced without any type of preparation. In the study of Aegon (2014) is observed that Spain occupies the thirteenth place in the preparation to retirement ranking. From this fact arises the purpose of this study: to know how retirement is perceived in different moments during the labour life. To do so, are analysed personal approaches to the disengagement from the labour world. It also seeks to know if the organizations of the interviewees carry out policies of disengagement for workers. Thus, we will be able to investigate the needs of support of workers in this new stage and suggest action proposals that allow to establish more satisfactory plans of detachment from the working world that should facilitate the adaptation of the workers to this new stage. The methodological approach is qualitative. To obtain the sample, we used the snowball technique, with which a total of 15 participants were obtained. Participants were classified into 3 groups according to their ages: from 50 to 55 years, from 55 to 60 years and from 60 to 65 years. Afterwards we studied the obtained results by an analysis of the thematic content. We found a diversity of perceptions regarding retirement based on the personal path; nonetheless, all of them had a common ground: the importance of the social and folkloric support (to carry out leisure activities) of this stage. Unlike what might be expected, retirement is not perceived negatively and is seen as a moment of individual decision-making. Participants indicated that they do not receive any kind of support from the company, but they would positively value the existence of retirement transition programs. In conclusion, we must focus our attention to retired people or those close to retirement and facilitate their adaptation to this new stage; thus, it seems necessary to propose retirement plans that benefit both organization and employee.